Assessing and enhancing the ecological validity of human locomotion in virtual reality - Sato, Kazuyuki; Suda, Yuki; Higuchi, Takahiro (Frontiers in Virtual Reality, 2026)
The increasing use of virtual reality (VR) technologies in behavioral research raises a critical question: to what extent do behaviors in VR mirror those in the real world? VR offers strong experimental control and reproducibility, yet its ecological validity remains debated. This review examines two fundamental human locomotion behaviors, overground walking and collision avoidance in immersive VR, and evaluates how accurately these behaviors are reproduced. Practical strategies for enhancing ecological validity that do not require specialized hardware development are also proposed. Evidence indicates that fundamental behavioral patterns are largely preserved, supporting the use of VR as a valuable tool for investigating human locomotion. However, participants consistently adopt more conservative behavioral strategies in VR, such as slower walking speeds, increased interpersonal distances, and earlier avoidance initiation, largely due to egocentric distance underestimation and head-mounted display constraints such as restricted field of view, limited resolution, and latency. To address these limitations, we suggest design approaches supported by prior evidence, including enhanced ground textures, full-body avatars, and optimal calibration procedures, all of which can enhance behavioral realism in VR. This review provides a comprehensive account of the ecological validity of VR locomotion and offers actionable strategies to enhance behavioral realism, providing valuable guidance for future studies using VR.